Traumatic central cord Syndrome: An integrated neurosurgical and neurocritical care perspective - Karol Martínez-Palacios; Andrés M. Rubiano; Andreas K. Demetriades; Sebastián Vásquez-García (Brain and Spine)
Traumatic Central Cord Syndrome (TCCS) presents complex challenges in the management of spinal cord injury. Characterized by disproportionate upper limb weakness, TCCS is the most common clinical spinal cord syndrome, typically affecting males in a bimodal age distribution. Mechanisms include hyperextension injuries in older adults with degenerative cervical spine disease and high-energy trauma in younger individuals. Diagnosis is based on neurological assessment, with the American Spinal Injury Association (ASIA) Impairment Scale used for severity classification. Management strategies, including surgical and medical approaches, may influence functional outcomes, although high-quality comparative evidence is limited. Surgical decompression and stabilization are often pursued to relieve mechanical compression, while nonoperative strategies may be considered in selected cases with less severe neurological deficits. The timing of surgical intervention remains a subject of ongoing debate and must be individualized. Neurocritical care considerations are increasingly recognized as potentially important in the early phase of TCCS. Experimental and clinical investigations into intraspinal pressure (ISP), mean arterial pressure (MAP), and spinal perfusion pressure (SPP) monitoring suggest these parameters may aid in minimizing secondary injury, though their routine clinical use is not yet established. Complications such as venous thromboembolism, infection, pressure injuries, and autonomic dysfunction are common and require comprehensive management. The role of corticosteroids remains controversial.This narrative review synthesizes current knowledge on TCCS, with emphasis on diagnostic, surgical, and neurocritical care considerations. As the field advances, further evidence is needed to clarify optimal management pathways and improve outcomes in this challenging clinical entity.